An Analysis of Students’ Problems on Reading Comprehension in Online Learning at the Ninth Grade Students of Junior High School 2 Jambi City - Elma Rita Pandiangan; Wennyta Wennyta; Kartika Dewi (JELT: Journal of English Language Teaching, 2021)
This research was aimed to find out the student problems on online learning in reading comprehension. This research took this title to find out what are the problems of students in reading comprehension on online learning. The setting of the research was in Junior High School 2 and the subject of the research was the Ninth Grade Students. The problems in reading online that there are five aspects of reading comprehension were determining main idea, making inference, identifying reference, finding specific information, and the understanding meaning of words or vocabulary. The research methodology of This research was a qualitative phenomenological approach research which involve purposive sampling. The total of respondents who researched this was twenty-two ninth grade of students. The results of the study explained that most of the ninth grade students had problems answering the test questions that had been given. The result is that only a few students understand the comprehension after they read about it. The cause of student problems in online learning is the lack of understanding of the meaning of the test so that they have problems in determining the information contained in a test. Lack of knowledge about vocabulary so that they have problems in learning reading comprehension.Keywords: Students’ Problems, Online Learning, Reading Comprehension.